IDEOLOGY CONSTRUCTION ON THE PRESIDENTIAL ELECTION NEWS 2014 OF KOMPAS NEWSPAPER - PUTRI, VANYA AMALIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Ideology Construction, Presidential Election News 2014, KompasNewspaper. Human uses language to communicate each other. In society, language is used to get the massage and to understand the meaning. From the language, human creates the meaning. The researcher conducts a research about the ideology construction on the presidential election news 2014 of Kompas newspaper. The researcher uses three dimensions of discourse by Norman Fairclough. This research focuses on two research problems, 1.) how Kompas newspaper constructs its readers’ opinion toward the candidates of Indonesian president through the lexical choices and 2.) how the constructed meanings are interpreted by the readers.This research uses qualitative approach in analyzing the constructed meaning from the lexical choices, how Kompas newspaper constructs the public opinion to how the constructed meanings are interpreted by the readers. The data used is the news of Kompas newspaper and the interview from the subscribers.This research suggests that the readers' opinion is constructed through lexical choices attributing both positive and negative character. The researcher finds five (5) positive sides and six (6) negative sides of the first candidate. Thisresearch also finds seven (7) positive sides dan one (1) negative side of the second candidate. From that finding, the researcher finds that Kompas newspaper is not as neutral as it is said. The neutrality of Kompas newspaper itself can be seen by the lexical choice and also the history. The public opinion is constructed after reading Kompas newspaper. But, this research finds that the readers do not only read one media, but also the others. Because of that, the voting behavior is not affected by reading it.Through this research, it is suggested the next researcher interested in doing similar research to consider different objects like slogan of fast food restauran, movie, photo, or book. It is also suggested that the next researcher should explore other theories, such as the theory of Van Dijk, Wodak, etc.